Development and validation of the Collective Efficacy Scale for Basketball - Ikeda, I.; Uchiyama, H.; Yoshida, K.; Iwai, K. (International Journal of Sport & Health Science, 2014)
Discussions on "collective efficacy" (CE; Bandura, 1986; 1997) in recent research have provided important knowledge about group functions. However, suitable CE scale for the field of sports coaching has not yet been developed. The purpose of present study was to develop a more general and versatile measure, by reconstructing the Collective Efficacy Scale for Basketball developed by Ikeda and Uchiyama (2012), and to verify its validity and reliability. Moreover, we investigated relationships among CE and gender, performance level. Factor analysis revealed that the Collective Efficacy Scale for Basketball Offense (CESBO) comprised 21 items within the following subscales of "Tactics", "Characteristics" and "Adjustments", and its construct validity was certified. With a Cronbach's alpha and an intraclass correlation coefficient (ICC), the CESBO was confirmed to have high reliability. Regarding concurrent validity, the Japanese versions of GEQ and CEQS was used as an external criterion. The results supported our hypotheses (p < .05). Also, the result of a two-tailed unpaired t-test indicated that no difference in CESBO was found between female and male athletes (p < .05). Furthermore, one-way ANOVA showed that higher performance level group had a significantly higher CE score (p < .05). According to analysis of effect size, it was suggested that the influence of CE on the collective performance is differed by competition categories. These findings of present study establish support for usefulness of the CESBO.